PENGARUH PENEMPATAN PEGAWAI SERTA BUDAYA KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABLE INTERVENING DI PT PLN (PERSERO) UIP SULBAGUT - Lambey, Buddhidhamma; Lengkong, Victor P.K.; Wenas, Rudy S. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2020)
PT PLN (Persero) UIP SULBAGUT is a PLN unit tasked with building electricity infrastructure in the provinces of North Sulawesi, Gorontalo and Central Sulawesi. The dynamic conditions of employees as well as changes in organizational culture that are currently taking place at PLN, has became an interesting to study, especially in terms of job satisfaction and employee performance. This study aims to analyze the effect of employee placement and work culture on employee performance with job satisfaction as an intervening variable at PT PLN (Persero) UIP SULBAGUT.The approach used is a quantitative approach. The population in this study were all employees at PT PLN (Persero) North Sulawesi Main Unit, amounting to 146 people. The sampling technique used is a census in which the entire population is sampled in this study. Because of that, the sample from this study were 146 respondents. Data collection methods for primary data are carried out using questionnaires distributed to employees. The data analysis technique used is the path analysis test. This study found that, it turns out that employees who are not satisfied in working are still able to provide good performance. This is because the employees at PT PLN (Persero) UIP SULBAGUT, even though they are not satisfied with their work, they still try to provide the best performance, with the hope that they can be looked at or drawn to other PLN units that are ideal or even hometown from the employee concerned. The same thing happens in company culture, where employees are still not satisfied with the new company culture, but still try to implement the rules of the company culture in the hope that if they show that they have a good performance and integrity, it can help the employee concerned to apply for a move to other PLN units that are ideal or even the hometown of the employee concerned.